2013
DOI: 10.1155/2013/308651
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 1‐Triacontanol on the Growth, Flowering, and Quality of Potted Bougainvillea Plants (Bougainvillea glabra var. “Elizabeth Angus”) under Natural Conditions

Abstract: Selected physiological and biochemical parameters were monitored at the vegetative and reproductive growth stages in potted Bougainvillea plants treated with five different concentrations of TRIA. Advanced flowering, flower bud number, and blooming rate increased significantly with 0.5 and 1.0 mg/L TRIA treatments. Similarly, photosynthetic rate, pigment content, quantum yield, and stomatal conductance increased significantly with 2.5, 1.0, and 5.0 mg/L TRIA treatments. Higher levels of N, P, and K, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
(39 reference statements)
1
14
0
4
Order By: Relevance
“…Carbon dioxide is important for okra plant as it is required in production of carbohydrates during photosynthesis process. Khandaker et al (2013b) reported that that stomatal conductance affects the net photosynthetic rate by regulating CO 2 fixation in the leaf mesophyll tissue and is positively correlated with photosynthesis. The results showed that different dose of NPK fertilizer produced significant effect on the stomatal conductance of okra leaf.…”
Section: Internal Carbon Dioxide (Co 2 ) and Stomatal Conductancementioning
confidence: 99%
“…Carbon dioxide is important for okra plant as it is required in production of carbohydrates during photosynthesis process. Khandaker et al (2013b) reported that that stomatal conductance affects the net photosynthetic rate by regulating CO 2 fixation in the leaf mesophyll tissue and is positively correlated with photosynthesis. The results showed that different dose of NPK fertilizer produced significant effect on the stomatal conductance of okra leaf.…”
Section: Internal Carbon Dioxide (Co 2 ) and Stomatal Conductancementioning
confidence: 99%
“…with 6.64% and 32.52%. These two active compounds have interesting biological activities as tumor inhibitor and plant hormone, respectively [20][21][22][23] ( Table 2). Using SFE method, very high extraction selectivity could be achieved, but with lower product yield (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Triacontanol is an effective growth regulator that can significantly improve plant growth (Tantos et al, 1999;Tantos et al, 2001;Malabadi and Nataraja, 2007;Perveen et al, 2010;Aziz et al, 2013;Khandaker, 2013;Perveen et al, 2014). This growing regulatory substances are effective on the biosynthesis of secondary metabolites and role plays to set up the process associated with the physiology and biochemistry of plants (Jaybhay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Triacontanol given to the seed of some weeds and horticultural crops have an influence on the germination and its morphology (Hoagland, 1980). According to Khandaker et al (2013) that triacontanol sprayed on the leaves can stimulate growth, increase inflorescence, and improve the quality of crops. Samui and Roy (2007) also reported that no phytotoxic effect and no detrimental effect is given to plants and predators, respectively.…”
Section: Introductionmentioning
confidence: 99%